Upaya Hukum Pihak Ketiga Untuk Melakukan Perlawanan Terhadap Sita Jaminan - Sugih Ayu Pratitis (Universitas Islam Sumatera Utara, 2019)
It is important to remember that credit risk is not only caused by the inability or unwillingness to pay from the debtor under normal circumstances. However, this can also be caused by other unexpected factors, such as natural disasters that have a direct impact on the debtor's business continuity. Therefore, there are efforts to rescue credit, including credit restructuring or providing new credit in the hope of restoring the business of debtors affected by the disaster. In order to assist in the recovery of these conditions, Bank Indonesia as the banking authority makes various efforts, among others, by issuing regulations to restore banking activities in the area of natural disasters. The problem in this study is how the efforts of third parties fight against seizure guarantees that have legal force, how the court attempts to delay the execution, how the legal consequences of resistance to seizure guarantees by third parties can result in the law being seized. This research is descriptive analysis. It is a study that describes the facts and data regarding the delay in credit payments in the disaster area of Sinabung eruption. This research applies library research and field research. Based on the results of the study, the policy carried out was related to the postponement of credit payments by debtors after the eruption of Mount Sinabung to date. Bank Indonesia has not yet determined specific policies and imposed special provisions on bank customers in the Mount Sinabung eruption area. This is because the Mount Sinabung disaster is not yet a national disaster, so the policy of delaying payments for customers still depends on the policies of each bank in the Karo district, as the affected area of the Sinabung eruption. The Civil Code's view of the policy of postponing credit payments after the eruption of Mount Sinabung was a natural thing to do, considering that the debtors failed to fulfill due to the incompetence of the debtor because of the force of the debtor. Mount Sinabung is by way of rescheduling, reconditioning, restructuring the restructuring of loans given to the victims of the sinabung eruption victims.